Formulation of pea milk fortified dahi incorporated with jamun seed extract - Pandhi, Shikha; Poonia, Amrita (Indian Journal of Dairy Science, 2021)
Changing market trend have paved the way for development of value-added products fortified with plant-based constituents for supplementing their therapeutic potential. In sight of this, fortified dairy products have gained immense attention in recent times. The present study was undertaken with an aim to fortify animal-based nutrients with plant-based nutrients by developing a pea milk fortified dahi incorporated with jamun seed extract. A ratio of 5:1 (5 parts of water and 1 part of pea) for pea milk formulation and 3:2 (3 parts of pea milk and 2 parts of skim milk) for fortification of milk was used for dahi preparation. The developed product exhibit good per cent antioxidant activity of 80.1±8.84 and total phenolic content of 98.33±15.56 mg of gallic acid equivalent (GAE)/ml of dahi sample with an overall acceptability of 8.6 on 0 day followed by an overall acceptability score of 6.2 on 12th day of storage which is the predicted shelf life of the product with successive decline in per cent antioxidant activity and total phenolic content beyond this period. Other parameters such as water holding capacity, viscosity and syneresis were found to be 60.35 ±1.34 %, 38±0.2cP and 8.2±0.4 ml/100g, respectively. Physicochemical parameters and textural analysis was also performed. The final cost of product was estimated to be Rs.13 per cup (100g) which is quite comparable to the market dahi.